The Effectiveness of Continuous Regional Arterial Infusion Therapy with Meropenem in Severe Acute Pancreatitis Compared with Imipenem: A Prospective, Randomized Study - Ogura, Shinji; Tanjou, Katsuhisa; Shinohara, Katsuhiro; Shirai, Kunihiro (The Japanese Journal of Gastroenterological Surgery, 2008)
Introduction: We performed a prospective randomized controlled trial in patients with severe acute pancreatitis, comparing one group who were given meropenem (MP group) and another group who received imipenem (IP group) using continuous regional arterial infusion (CRAI), and the effect of meropenem was reviewed. Methods: At admission, 30 subjects were randomly allocated to either the MP group (n=16) or the IP group (n=14). We then conducted continuous hemodiafiltration, selective decontamination of the digestive tract, and enteral nutrition. We looked at the start time and duration of CRAI, the catheterization locus, and specific treatment enforcement rates. We also compared our findings to Ministry of Health, Labour and Welfare severity scores, the APACHE II score, the SOFA score, and the CRP level both at admission and two weeks after. We then reviewed the infection rate, pancreatitis-related complications frequency, infected pancreatic necrosis rate, surgical treatment rate, mortality, infection site, and presence of causative organisms. Results: The two groups had no significant differences in age, cause, CRAI start time and duration, catheterization locus, or specific treatment enforcement rates. No significant intragroup differences were seen in any scores or CRP levels either at admission or two weeks after. No significant differences in infection rates were seen between groups (MP group: 37.5%, IP group: 42.9%). No significant intragroup differences were seen, either, in incidence of infection and pancreatitis-related complications, the rate of infected pancreatic necrosis, the surgical treatment rate, or mortality. The infection site had a great deal of expectoration requiring catheterization, and causative bacteria did not differ between the groups. We did, however, observe the presence of isolated antimicrobial resistance pathogens and polymicrobial infection. Conclusions: Meropenem was found to be effective in preventing of infection in severe acute pancreatitis when initiated within 72 hours after onset. Its effectiveness closely parallels that of imipenem.